Cognitive Factors and Cochlear Implants: Some Thoughts on Perception, Learning, and Memory in Speech Perception - Pisoni, David B. (2000)
Over the past few years, there has been increased interest in studying some of the cognitive factors that affect speech perception performance of cochlear implant patients. In this paper, I provide a brief theoretical overview of the fundamental assumptions of the information-processing approach to cognition and discuss the role of perception, learning, and memory in speech perception and spoken language processing. The information-processing framework provides researchers and clinicians with a new way to understand the time-course of perceptual and cognitive development and the relations between perception and production of spoken language. Directions for future research using this approach are discussed including the study of individual differences, predicting success with a cochlear implant from a set of cognitive measures of performance and developing new intervention strategies.